Comparison of the Quality of life for People with and without Disabilities in Saudi Arabia who use Lower Limb Prosthetics or Orthoses: Social Attitudes towards Prosthetic Users in Saudi Arabia (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this study is to determine how people in Riyadh, Saudi Arabia, feel aboutprosthetic patients and how much the community accepts them. People who have lost a physical limbdue to trauma, disease (such as gangrene), or congenital disorders are able to function and face life asnormal humans with the help of prostheses, which are devices called prosthetics. It is commonknowledge that prostheses help people with special needs adjust to their environment and enjoy ahigher quality of life. Even though this makes sense, the way the community sees and acceptsprostheses has not been fully studied because people with prostheses can't take part. In addition, wediscovered that the majority of participants have a negative attitude towards those who have prostheses.reasons that were not investigated since there were no significant variations in age, gender, oreducational status that might perhaps account for the low percentage of acceptance.